2009
DOI: 10.1016/j.physc.2009.03.044
|View full text |Cite
|
Sign up to set email alerts
|

ARPES studies of the electronic structure of LaOFe(P,As)

Abstract: We report a comparison study of LaOFeP and LaOFeAs, two parent compounds of recently discovered iron-pnictide superconductors, using angle-resolved photoemission spectroscopy. Both systems exhibit some common features that are very different from well-studied cuprates. In addition, important differences have also been observed between these two ferrooxypnictides. For LaOFeP, quantitative agreement can be found between our photoemission data and the LDA band structure calculations, suggesting that a weak coupli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
81
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 35 publications
11
81
3
Order By: Relevance
“…1 (b), the momentum regions with strong intensities are opposite between the large and small FS sheets around the Γ point, implying that they have different orbital characters. The large size of the hole pocket has been reported by the previous ARPES studies for the 1111 iron-based superconductors 13,17,18,22 and reflects heavily hole-doped electronic states. One can also observe clover-shaped FS's around the corner (the M point) of the 2D BZ.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…1 (b), the momentum regions with strong intensities are opposite between the large and small FS sheets around the Γ point, implying that they have different orbital characters. The large size of the hole pocket has been reported by the previous ARPES studies for the 1111 iron-based superconductors 13,17,18,22 and reflects heavily hole-doped electronic states. One can also observe clover-shaped FS's around the corner (the M point) of the 2D BZ.…”
mentioning
confidence: 52%
“…Because the 1111 system has higher T c 's than those of the 122 system, detailed knowledge of their electronic structure and their differences from that of the 122 system may give a clue for understanding the mechanism of superconductivity in the iron-based superconductors. In the previous ARPES studies on the 1111 system 13,18 , heavily hole-doped electronic states have been observed probably due to the polar nature of the cleaved surfaces.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…22,23 In this case, surface bands result from the polar nature of these surfaces. 23 Surface states of this kind are not expected for LiFeAs and NaFeAs since the (001) surface of these compounds is not polar and they are indeed not seen by ARPES.…”
Section: Discussionmentioning
confidence: 99%
“…These paths were chosen as they allow us to compare our results with available ARPES data, in particular those of Refs. 65,[72][73][74] . Concretely, we here show the evolution of the spectral function A( k, ω) as a function of momentum k, at low temperature: T = 20 K, and at half-filling: n = 2 (i.e.…”
Section: B Momentum Dependence Of the Spectral Densitỹmentioning
confidence: 99%